Uptake of the β-Lactam Precursor α-Aminoadipic Acid in Penicillium chrysogenum Is Mediated by the Acidic and the General Amino Acid Permease - Trip, Hein (American Society for Microbiology, 2004)
External addition of the β-lactam precursor α-aminoadipic acid to the filamentous fungus Penicillium chrysogenum leads to an increased intracellular α-aminoadipic acid concentration and an increase in penicillin production. The exact route for α-aminoadipic acid uptake is not known, although the general amino acid and acidic amino acid permeases have been implicated in this process. Their corresponding genes, PcGAP1 and PcDIP5, of P. chrysogenum were cloned and functionally expressed in a mutant of Saccharomyces cerevisiae (M4276) in which the acidic amino acid and general amino acid permease genes (DIP5 and GAP1, respectively) are disrupted. Transport assays show that both PcGap1 and PcDip5 mediated the uptake of α-aminoadipic acid, although PcGap1 showed a higher affinity for α-aminoadipic acid than PcDip5 (K(m) values, 230 and 800 μM, respectively). Leucine strongly inhibits α-aminoadipic acid transport via PcGap1 but not via PcDip5. This difference was exploited to estimate the relative contribution of each transport system to the α-aminoadipic acid flux in β-lactam-producing P. chrysogenum. The transport measurements demonstrate that both PcGap1 and PcDip5 contribute to the α-aminoadipic acid flux.